Perjanjian Kerjasama Pembiayaan Kesehatan Masyarakat sebagai Landasan Sistem Kesehatan Nasional - Lenny Lenny; Marice Simarmata (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
A cooperation agreement is a legal instrument that underlies the regulation of rights, obligations, and responsibilities between the parties involved in a collaboration. In the context of public health financing, this agreement aims to ensure access to adequate health services, especially for disadvantaged groups. Along with the reform of the health sistem in Indonesia in recent years, the government has sought to improve accessibility and quality of services through the transformation of the health financing sistem. The National Health Sistem (SKN) as the main framework is organized to ensure equitable health services. One of the crucial components in the SKN is health financing which is realized through the National Health Insurance (JKN). Legal provisions regarding the form and mechanism of this collaboration have been regulated in Law Number 17 of 2023, specifically Article 4 paragraphs (1) and (2), which emphasize that collaboration between BPJS and central and regional government institutions is carried out through a written agreement, which can be in the form of a memorandum of understanding, operational cooperation, functional cooperation, or other forms mutually agreed upon.